MAKNA SIMBOLIK TRADISI NYADRAN - Fuad, A.Jauhar (Dinamika, 2013)
Nyadran is the heritage of hindu, nowadays it has transformed after islam spread in java. This transformation produced local tradition without mitting the Islamic dogma and local tradition. The tradition has religious meaning concering with thanksgiving performance to Allah and wishing Allah SWT will receive the best from their ancient people or family. Nyadran is one of media for them to hope the safety life and welfare even it can illuminate the cultural transformation among them